Synthesis of N-methyl 3-alkyl-isothiazolidine- 1,1-dioxo-3-methylcarboxylates through the intramolecular Michael reaction - Izhyk, V.V.; Dobrydnev, A.V.; Popova, M.V.; Volovenko, Yu.M. (Reports of the National Academy of Sciences of Ukraine, 2022)
An efficient and common method for the synthesis of N-methyl 3-alkyl-isothiazolidine-1,1-dioxo-3-methylcarboxylates has been developed. Readily available 2-monosubstituted β-amino acid esters hydrochlorides and β-chloroethylsulfonyl chloride were used as starting reagents. Methyl 2-alkyl-2-(vinylsulfonamido)ethanoates obtained on the first step were alkylated at the Nitrogen atom and converted into methyl 2-alkyl-2-(N-methylvinylsulfonamido) ethanoates. The latter were subjected to NaH-mediated intramolecular Michael addition thus affording the target methyl 3-alkyl-isothiazolidine-1,1-dioxo-3-methylcarboxylates. This class of compounds is considered as sulfonamide bioisostere of natural pyroglutamic acid (pGlu) and thus can be used in the synthesis of compounds with potential biological activity.